Cognitive ability in childhood and the chronicity and suicidality of depression - Hung, Galen Chin-Lun (Br J Psychiatry, 2016)
Background There is inconsistent evidence regarding the influence of general cognitive abilities on the long-term course of depression. Aims To investigate the association between general childhood cognitive abilities and adult depression outcomes. Method We conducted a cohort study using data from 633 participants in the New England Family Study with lifetime depression. Cognitive abilities at age 7 were measured using the Wechsler Intelligence Scale for Children. Depression outcomes were assessed using structured diagnostic interviews administered up to four times in adulthood between ages 17 and 49. Results In analyses adjusting for demographic factors and parental psychiatric illness, low general cognitive ability (i.e. IQ<85 v. IQ>115) was associated with recurrent depressive episodes (odds ratio (OR) = 2.19, 95% CI 1.20–4.00), longer episode duration (rate ratio 4.21, 95% CI 2.24–7.94), admission to hospital for depression (OR = 3.65, 95% CI 1.34–9.93) and suicide ideation (OR = 3.79, 95% CI 1.79–8.02) and attempt (OR = 4.94, 95% CI 1.67–14.55). Conclusions Variation in cognitive abilities, predominantly within the normal range and established early in childhood, may confer long-term vulnerability for prolonged and severe depression. The mechanisms underlying this vulnerability need to be established to improve the prognosis of depression among individuals with lower cognitive abilities.